The Utilization of Glyphosate by Bacteria Isolated from Soil - Adebayo Oyewole, Solomon Bankole Oyeleke & Olabisi Peter Abioye, Faith Onyinyechi Mbagwu, Oluwafemi (Covenant Journal of Physical and Life Sciences, 2019)
Glyphosate is one of the most commonly used herbicides worldwide. It is primarily applied to agricultural lands. This study examined the utilization of glyphosate by bacteria isolated from soil. Five bacteria were isolated, namely; Bacillus cereus, Bacillus subtilis, Escherichia coli, Pseudomonas sp., and Actinomyces sp. Bacillus cereus and Bacillus subtilis were selected for the studies based on their rapid degradation of the herbicides. The ability of the isolates to degrade different concentrations of glyphosate were tested in minimal salt medium (MSM) and incubated on a rotary shaker at 120 rpm at 30oC for 28 days. The effects of Pb2+ and Cd2+ on degradation of the isolates were also determined at concentrations of 200 µg/ml, 300 µg/ml and 400 µg/ml in 150 ml of the MSM. The bacteria were isolated using pour plate method and identified based on their cultural and biochemical characteristics. The two isolates were identified as Bacillus cereus BFM4 and Bacillus subtilis H184 using polymerase chain reaction and sequence analysis. There were significant differences (P < 0.05) in the percentage utilization of the herbicides by the test organisms in all the treatments at day 28. Bacillus cereus BFM4 had the highest percentage utilization of 97.04 % and 90.49 % of glyphosate at the lowest concentration 20 mg/ml and 400 µg/ml of Pb2+. The results of this study showed that the isolates were able to utilize varying concentration of glyphosate with an increased utilization on addition of Pb2+ and Cd2+.